Relatively high light inhibits reserves degradation in the Coptis chinensis rhizome during the leaf expansion by changing the source-sink relationship - Ke, Wenjia; Li, Yirou; Zhong, Furong; Pen, Maoyao; Dong, Jijing; Xu, Binjie; Ma, Yuntong; Zhou, Tao (Frontiers in Plant Science, 2023)
The early spring is a seasonal high-light “window” for new leaf growth and photosynthetic carbon capture by the shade-tolerant evergreen understory plants. However, it remains unclear how light regulates the source–sink relationship between rhizome (RO), mature leaf (ML), and immature leaf (IL) during Coptis chinensis leaf expansion. Understanding this relationship is essential to reducing RO reserve degradation and ultimately promote RO biomass accumulation. The plants grew in an artificial climate chamber with low (50 μmol m−2 s−1) and relatively high (200 μmol m−2 s−1) light intensity treatments. Leaf fluorescence, foliar phosphorus (P) fractions, soluble sugars, starch, total P, and alkaloid concentrations in ILs, MLs, and RO were measured, and 13C labeling was used to indicate the direction of photosynthetic carbon flow between organs. The plants grown under high light intensity had higher levels of starch in RO and higher RO biomass at the end of the year compared to those grown under low light intensity. The photosystem II (PSII) operating efficiency [Y(II)], relative electron transport rate (rETR), and photochemical quenching (qP), as well as sucrose and glucose, in ILs and MLs under relatively high light, was higher than those under low light. The glucose and starch concentrations in ILs at 35 d was significantly higher than that at 15 d when plants were under 200 μmol m−2 s−1, while they were not significantly changed and remained low at 50 μmol m−2 s−1. The 13C was detected in the RO when plants were grown at 200 μmol m−2 s−1, regardless of ILs and MLs 13C labeling, while no 13C was detected in the RO when plants were under 50 μmol m−2 s−1. Additionally, the proportion of photosynthetic transport from ILs to MLs was significantly higher than that from MLs to ILs under the 50-μmol m−2 s−1 limit. Total P concentration in ILs was lower under relatively high light, but there was no difference in nucleic acid P concentration in ILs under the two light intensity treatments. The alkaloid concentration in RO was lower under 200 μmol m−2 s−1 than that under 50 μmol m−2 s−1. We propose that relatively high light reduces the need for carbohydrates and P stored in the RO to support IL growth by (1) accelerating the sink-to-source transition in ILs, which inhibits the use of reserves in the RO; (2) using energy from MLs to support IL growth, thereby reducing RO reserve consumption, and (3) reducing the demand for P by investing less in the development of photosynthetic machinery. Furthermore, under low light, MLs serve as a sink and rely on other organs for support, directly or indirectly exacerbating the reserves lost in the RO.